Diyalojik İletişim Teorisi Perspektifinden Ülkelerin Sağlık Bakanlıkları Web Sitelerine Yönelik Bir Değerlendirme - (:unkn) unknown (My University, 2021)
Dünya genelinde insanları etkileyen Covid-19 Salgını bireyin, toplumun doğru bir şekilde bilgilendirilmesi ve yönlendirilmesi açısından iletişimin öneminin daha net bir şekilde anlaşıldığı dönem olarak devam etmektedir. Küresel düzeyde kamusal bir sorun olan Covid-19 Salgını’na yönelik farkındalığın oluşturulması, tutumların değiştirilmesi, doğru bilgi akışının sağlanması gibi insan sağlığını doğrudan etkileyen konularda diyalojik iletişime olanak tanıyan kurumsal web sitelerine ihtiyacın arttığı görülmektedir. Bu çerçeveden hareketle çalışmada Covid-19 Salgın Dönemi’nde en yüksek genel vaka istatistiğine sahip ilk 50 ülkenin Sağlık Bakanlıklarına ait Web sayfaları Kent ve Taylor’ın diyalojik iletişim kriterleri çerçevesinde karşılaştırmalı olarak içerik analizine tabi tutulmuş; bu analizle örneklem olarak seçilen ülkelerin Sağlık Bakanlıkları-web sitelerinin diyalojik iletişim düzeyleri belirlenerek diyalogun ne oranda ve nasıl gerçekleştiği ortaya konulmaya çalışılmıştır. Araştırma sonucunda, Sağlık Bakanlıklarına ait web sitelerinin büyük bir bölümünde; anket, canlı destek ve soru-cevap uygulamasına imkân tanıyan özelliklerin yer almadığı dolayısıyla web sitelerinin diyalojik döngü ve yeniden ziyareti sağlama açısından yeterli düzeyde olmadıkları saptanmış, bu eksikliklerin giderilmesiyle diyalojik iletişim için daha uygun bir ortamın oluşacağı sonucuna ulaşılmıştır.

Covid-19 pandemic, which has been affecting people globally, continues as a period thanks to which it is clearly understood that communication is quite important by means of informing and instructing the society and the individuals in a correct way. It is seen that the need for institutional web sites that enables dialogic communication has increased in terms of subjects that directly affects human health; such as creating awareness about Covid-19 which is a globally-public problem, changing the behaviors, and providing the flow of correct information. Within the scope of this frame, the web sites belonging to the health departments of 50 countries that have the highest general case statistics in Covid-19 Pandemic Period are comparatively subjected to a content analysis by applying the dialogic communication criteria of Kent and Taylor; the dialogic communication levels of Ministries of Health - web sites of the countries that are chosen as samples are specified in consequence of the analysis, and it is aimed to determine the facts that, at what rate and how the dialogues have been actualized, in this study. As a result of it, it is seen that there aren’t suitable applications which can be listed as questionnaires, online support and QA forms in most of the web sites of health departments, therefore that, they are not sufficient for providing dialogic loop and generation of return visits and it has been found that an atmosphere which is more suitable for dialogic communication can be provided if these shortages are removed.
An Evaluation of Countries' Ministry of Health Websites from the Perspective of Dialogical Communication Theory